2015
DOI: 10.1111/sbr.12122
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sleep postures and sleep-disordered breathing parameters in people with Down syndrome in Japan

Abstract: People with Down syndrome (DS) are prone to develop sleep-disordered breathing (SDB), especially obstructive sleep apnea (OSA) and they are reported to sleep in unusual sleep postures. The purpose of this study was to determine the relationship between sleep postures and SDB parameters, including the objective nocturnal oxygen desaturation in people with DS in Japan. Overnight pulse oximetry was measured in 32 people with DS (male 44%, mean age 18 ± 10 years) and a questionnaire was completed to obtain informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…Previous research also has noted that children with DS who employ unusual sleep postures had significantly better respiratory indices than had those children with usual sleep postures (Rahmawati et al . ). Although there was no difference in total scores of sleep problems between the child with usual sleep posture and the child with unusual sleep posture in this study, the sub‐scales of sleep duration and daytime sleepiness were significantly increased in children with unusual sleep posture.…”
Section: Discussionmentioning
confidence: 97%
“…Previous research also has noted that children with DS who employ unusual sleep postures had significantly better respiratory indices than had those children with usual sleep postures (Rahmawati et al . ). Although there was no difference in total scores of sleep problems between the child with usual sleep posture and the child with unusual sleep posture in this study, the sub‐scales of sleep duration and daytime sleepiness were significantly increased in children with unusual sleep posture.…”
Section: Discussionmentioning
confidence: 97%
“…In children with DS, Nisbet et al also reported that the apnoea hypopnea index was higher during sleep in the supine position than in the non‐supine position in the non‐rapid eye movement sleep period (Nisbet et al ). We recently reported that children with DS who have prone and unusual sleep postures had significantly better respiratory indices compared with those with usual sleep postures during sleep (Rahmawati et al ). Senthilvel and Krishna also reported that the apnoea hypopnea index was lowest during the prone and leaning forward positions in children with DS (Senthilvel & Krishna ).…”
Section: Discussionmentioning
confidence: 99%
“…The parents completed a questionnaire on age, sex, body weight, body height, presence of CHD, and SDB-related signs and symptoms, such as witnessed midnight arousal, snoring, apnea, and daytime napping [ 17 , 18 ]. The Japanese version of the Epworth Sleepiness Scale (ESS) was also answered by the parents, and a higher ESS value indicated that the person had more severe daytime sleepiness [ 10 , 19 ]. Witnessed apnea was defined as a complete pause of breathing followed by restarting of breathing with rapid gasping for air [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…The American Academy of Pediatrics recommends a sleep study to screen for SDB in children with DS, even at early ages. However, a sleep study using type-1 polysomnography (PSG) has several disadvantages, including its high cost and the difficulty in performing the test with many sensors, especially in children with DS who also have intellectual disability [ 10 , 11 ]. Initial screening with pulse oximetry could be an alternative tool for cases in which a diagnostic multichannel PSG study is difficult to perform, and it might provide patients early access to essential therapy for SDB [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%